Improving Students’ Speaking Ability by Using Role Play - Doni Sudibyo; Ari Wibowo; Muhlasin Muhlasin (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
Role play is a tool of dramatic explorations, which engages participants within an aesthetic, there-dimensional problem-solving process to examine, explore, and reflect upon issue of personal and collective importance. The aim of study was to find out whether or not the use of role play of daily conversation in teaching speaking is able to improve the students’ speaking ability or not. This research used quasi-experimental method. The sample of the research is 30 students of first grade of SMA Muhammadiyah Aimas which was divided into two classes. The data has collected through interview on pre-test and role play show on post-test. The data analysis showed the improvements of the students’ speaking ability who are studied through role play. It was proven by the mean score of experimental class was 72.3 with SD 3,527 higher than control class was 65,7 with SD 4,154. In other words, Role Play techniques can improve the speaking ability of the students.